THREE-DIMENSIONAL IMAGING OF EARTH AND PLANETARY MATERIALS - Carlson W.D. (My University, 2006)
X-ray computed tomography, neutron computed tomography, and magnetic resonance imaging are driving novel scientific advances by enabling rapid, non-destructive, three-dimensional examination and analysis of earth and planetary materials. Discoveries catalyzed by these approaches range across fields from environmental geology to petroleum geology, hydrology to soil science, paleontology to petrology, and geodynamics to meteoritics. They have impacted our understanding of hydrocarbon reservoirs, contaminant transport, climate change, CO2 sequestration, the evolution of life, crustal uplift, mantle metasomatism, planetary differentiation, and more. Three-dimensional imaging is likely soon to become an essential component of every investigator's toolkit, especially as instruments and facilities emerge that are optimized for increasingly sophisticated geological applications of these techniques, and as access to them expands. © 2006 Elsevier B.V. All rights reserved.
Keywords: MAGNETIC RESONANCE IMAGING; NEUTRON COMPUTED TOMOGRAPHY; VISUALIZATION; X-RAY COMPUTED TOMOGRAPHY